Differential Cell Count and CRP Level in Blood as Predictors for Middle East Respiratory Syndrome Coronavirus Infection in Acute Febrile Patients during Nosocomial Outbreak - Park, Ga Eun; Kang, Cheol-In; Ko, Jae-Hoon; Cho, Sun Young; Ha, Young Eun; Kim, Yae-Jean; Peck, Kyong Ran; Song, Jae-Hoon; Chung, Doo Ryeon (Journal of Korean medical science, 2017)
A case-control study was performed to identify clinical predictors for Middle East respiratory syndrome coronavirus (MERS-CoV) infection among patients with acute febrile illness during the nosocomial outbreak. Patients with MERS-CoV were more likely to have monocytosis with normal white blood cell (WBC) count and lower C-reactive protein (CRP) level. Simple laboratory data such as complete blood counts (CBC) with differential count could be a useful marker for the prediction of MERS and triage at the initial presentation of acute febrile patients in outbreak setting.